Perancangan Sistem Informasi Gaji Berkala Pegawai di Kantor Walikota Medan - Casenda, Deanisa Luthfy; Syah, Rahmad (Universitas Medan Area, 2025)
The development of information technology has had a significant impact on increasing the efficiency and effectiveness of various administrative processes, including in personnel management in government agencies. This research aims to design and build a web-based periodic salary increase (KGB) information system at the Regional Civil Service and Human Resources Development Agency (BKDPSDM) of Medan City. This system was developed to replace the manual processes that are still used in the management of the KGB, which often causes delays and errors in the processing of employee data. This study uses the System Development Life Cycle (SDLC) method of the waterfall model, which includes requirements analysis, design with flowcharts, DFD, and ERD, implementation using CodeIgniter, and testing with the black-box method. The results of the study show that the system built improves the efficiency of data input, salary calculation, and automatic report generation. The notification feature helps reduce administrative delays, while the user-friendly interface makes it easy for staff to operate without intensive training. The implementation of this system is expected to increase the accuracy, speed, and transparency of personnel management in the Medan City BKDPSDM.